#Trending in the right direction : a case study analyzing Temple football's #SpringBall18 campaign - Sanderson, Jimmy; Stokowski, Sarah; Taylor, Elizabeth, active 2020 (London : Human Kinetics, Inc., 2020)
Social media play a major role in marketing and promotional efforts in intercollegiate athletics, yet student-athletes are rarely included in these campaigns. This case study analyzes a campaign employed by Temple University's football program that departed from this norm. During their 2018 spring game, Temple coaches allowed football players to put their Twitter handles on the backs of their jerseys. Through interviews with athletic department staff members and football student-athletes and analysis of football players' tweets and media framing of this campaign, several positive outcomes emerged. These included how the campaign fostered student-athlete buy-in and generated favorable media coverage for the program. However, analysis also revealed that while many football student-athletes actively used Twitter, they were not fully integrated into the campaign. Implications for including student-athletes' social media content in athletic department marketing, branding, and promotional efforts are discussed.
Originally Published InSanderson, J., Stokowski, S., & Taylor, E. (2019). #Trending in the Right Direction: A Case Study Analyzing Temple Football's #SpringBall18. International Journal of Sport Communication, 12(1), 104-127.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Temple Owls (Football team) -- Case studies; Mass media -- Marketing -- United States -- Case studies